2017
DOI: 10.1111/bcp.13245
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, safety, tolerability and immunogenicity of FKB327, a new biosimilar medicine of adalimumab/Humira, in healthy subjects

Abstract: The study demonstrated pharmacokinetic similarity of FKB327 with EU- and US-Humira. FKB327 was well tolerated by healthy subjects, with adverse effects similar to Humira. If clinical similarity to Humira, including efficacy, can be shown in patients, FKB327 will meet the criteria for biosimilarity to Humira.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
45
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 21 publications
(28 reference statements)
16
45
1
1
Order By: Relevance
“…In this study, the percentages of subjects over time with binding ADA formation and nADA formation were similar among all study arms. The results were also consistent with other recent studies evaluating biosimilars of Humira . In the M923 study, the proportion of subjects with a confirmed ADA response, the rate of ADA seroconversion over time, and the occurrence of nADAs were in line with that reported by Kaur et al .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the percentages of subjects over time with binding ADA formation and nADA formation were similar among all study arms. The results were also consistent with other recent studies evaluating biosimilars of Humira . In the M923 study, the proportion of subjects with a confirmed ADA response, the rate of ADA seroconversion over time, and the occurrence of nADAs were in line with that reported by Kaur et al .…”
Section: Discussionsupporting
confidence: 92%
“…A lower ADA response (44%) has been reported with LBAL, a Humira biosimilar that is currently in development . The ADA responses with M923 and other Humira biosimilars are higher (>70%) than historically reported for Humira registration trials or in a real‐world study in RA . The lower ADA response may reflect the fact that in some of these studies, patients may have also been receiving agents that could suppress the immune system and thereby reduce the incidence of antibody formation .…”
Section: Discussionmentioning
confidence: 84%
“…Although not directly studied, the risk of immunogenicity following a second dose in participants with CDI is also thought to be low because no treatment‐emergent ADA‐positive participants were observed in phase 3, and 1013 were categorized as negative. For drugs that are immunogenic, it is not uncommon to observe ADA following a single dose, particularly if the half‐life is in the multiweek range, as the drug remains systemically available to elicit a response from the immune system for a considerable amount of time . Bezlotoxumab has an elimination half‐life of approximately 19 days and, therefore, after a 10‐mg/kg dose, remains systemically available for several months and thus is also available to elicit a response from the immune system; for reference, at 180 days postdose, the mean bezlotoxumab concentration was ∼1 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Even for adalimumab, the first fully human monoclonal antibody, immunogenicity rates were initially reported as 1% with methotrexate coadministration and 10% as monotherapy. Today, after much scrutiny for adalimumab during biosimilar development activities by many different companies, it is now well recognized that 60%–70% of individuals develop ADAs . Further, even nonneutralizing activity of ADAs can cause increased clearance and thus reduced exposure and efficacy …”
Section: Common Characteristics Of Biologicsmentioning
confidence: 99%
“…Today, after much scrutiny for adalimumab during biosimilar development activities by many different companies, it is now well recognized that 60%-70% of individuals develop ADAs. 10 Further, even nonneutralizing activity of ADAs can cause increased clearance and thus reduced exposure and efficacy. 9 Biologics also share many pharmacokinetic characteristics.…”
Section: Common Characteristics Of Biologicsmentioning
confidence: 99%